Arabic Language Learning with Multicultural Perspective at State Islamic Universities in East Java - Syuhadak Syuhadak; Danial Hilmi; Inayatur Rosyidah (LISANIA: Journal of Arabic Education and Literature, 2021)
This study aimed at describing the model and implementation of Arabic language learning at State Islamic Universities (PTKINs) in East Java viewed from a multicultural perspective. This study is essential, considering the diversity of ethnicities and cultures in Indonesia, so unity in learning is needed. This qualitative study described the phenomenon and extracted data obtained from interviews with program managers and lecturers, as well as pre-pandemic observation and documentation of the learning implementation. The results showed that PTKINs in East Java implement an intensive program to equip students to master Arabic with adequate Arabic graduation standards. Its implementation is carried out both in the classroom through learning programs and outside the classroom activities to provide motivation and improve learning outcomes through structured activities.